THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND ACADEMIC OPTIMISM CULTURE ON TEACHER EMPOWERMENT AND MOTIVATION ALONG ITS IMPACT ON THE EFFECTIVENESS OF MEDAN STATE JUNIOR HIGH SCHOOL - Indra Prasetia; Sri Melfayetty; Rosmala Dewi (State Islamic University of North Sumatra Indonesia, 2020)
This study aims to determine the effect of transformational leadership and a culture of academic optimism on the empowerment and motivation of teachers and school effectiveness by causality, both direct and indirect effects in the path analysis framework. This research took place in Medan State Junior High School, amounting to 45 State Junior High Schools with a sample of 304 teachers. Simultaneously and partially it shows that (1) transformational leadership and academic optimism culture have a positive and significant effect on the empowerment of teachers at SMP Negeri Medan, (2) transformational leadership, academic optimism culture and empowerment have a positive and significant effect on the work motivation of teachers at SMP Negeri Medan, (2) 3) transformational leadership, academic optimism culture, empowerment and work motivation have a positive and significant effect on the effectiveness of Medan State Middle Schools.Keywords: Transformational Leadership, Academic Optimistic Culture, Empowerment, Work Motivation and School Effectiveness